Assessment of Cardiovascular Risk in Older Patients With Gout Initiating Febuxostat Versus Allopurinol: Population-Based Cohort Study. Issue 11 (11th September 2018) - Zhang, MaryAnn; Solomon, Daniel H.; Desai, Rishi J.; Kang, Eun Ha; Liu, Jun; Neogi, Tuhina; Kim, Seoyoung C.
Abstract : Background: Hyperuricemia and gout are associated with an increased risk of cardiovascular disease. Xanthine oxidase inhibitors, allopurinol and febuxostat, are the mainstay of urate-lowering treatment for gout and may have different effects on cardiovascular risk in patients with gout. Methods: Using US Medicare claims data (2008–2013), we conducted a cohort study for comparative cardiovascular safety of initiating febuxostat versus allopurinol among patients with gout ≥65 years of age. The primary outcome was a composite end point of hospitalization for myocardial infarction or stroke. Secondary outcomes were individual end points of hospitalization for myocardial infarction, stroke, coronary revascularization, new and recurrent heart failure, and all-cause mortality. We used propensity score matching with a ratio of 1:3 to control for confounding. We estimated incidence rates and hazard ratios for primary and secondary outcomes in the propensity score–matched cohorts of febuxostat and allopurinol initiators. Results: We included 24 936 febuxostat initiators propensity score–matched to 74 808 allopurinol initiators. The median age was 76 years, 52% were male, and 12% had cardiovascular disease at baseline. The incidence rate per 100 person-years for the primary outcome was 3.43 in febuxostat and 3.36 in allopurinol initiators. The hazard ratio for the primary outcome was 1.01 (95% CI, 0.94–1.08) in the febuxostat group compared with the allopurinol group. Risk of secondary outcomes including all-cause mortality was similar in both groups, except for a modestly decreased risk of heart failure exacerbation (hazard ratio, 0.94; 95% CI, 0.91–0.99) in febuxostat initiators. The hazard ratio for all-cause mortality associated with long-term use of febuxostat (>3 years) was 1.25 (95% CI, 0.56–2.80) versus allopurinol. Subgroup and sensitivity analyses consistently showed similar cardiovascular risk in both groups. Conclusions: Among a cohort of 99 744 older Medicare patients with gout, overall there was no difference in the risk of myocardial infarction, stroke, new-onset heart failure, coronary revascularization, or all-cause mortality between patients initiating febuxostat compared with allopurinol. However, there seemed to be a trend toward an increased, albeit not statistically significant, risk for all-cause mortality in patients who used febuxostat for >3 years versus allopurinol for >3 years. The risk of heart failure exacerbation was slightly lower in febuxostat initiators. Abstract : Supplemental Digital Content is available in the text.